Effect of starvation on branched-chain alpha-keto acid dehydrogenase activity in rat heart and skeletal muscle - Holecek, M (Physiological research, 2001)
The aim of the present study was to investigate changes in the activity of branched-chain alpha-keto acid dehydrogenase (BCKAD) in skeletal muscle and the heart during brief and prolonged starvation. Fed control rats and rats starved for 2, 4 and 6 days were anesthetized with pentobarbital sodium before heart and hindlimb muscles were frozen in situ by liquid nitrogen. Basal (an estimate of in vivo activity) and total (an estimate of enzyme amount) BCKAD activities were determined by measuring the release of 14CO2 from alpha-keto[1-(14)C]isocaproate. The activity state of BCKAD complex was calculated as basal activity in percentages of total activity. Both basal and total activities and the activity state of the BCKAD were lower in skeletal muscles than in the heart. In both tissues, starvation for 2 or 4 days caused a decrease in the basal activity and activity state of BCKAD. On the contrary, in the heart and muscles of animals starved for 6 days a marked increase in basal activity and activity state of BCKAD was observed. The total BCKAD activity was increasing gradually during starvation both in muscles and the heart. The increase was significant in muscles on the 4th and 6th day of starvation. The demonstrated changes in BCKAD activity indicate significant alterations in branched-chain amino acid (BCAA) and protein metabolism during starvation. The decreased BCKAD activity in skeletal muscle and heart observed on the 2nd and 4th day of starvation prevents the loss of essential BCAA and is an important factor involved in protein sparing. The increased activity of BCKAD on the 6th day of starvation indicates activated oxidation of BCAA and accelerated protein breakdown.
Keywords: ketokyseliny; velikost orgánu; Male; Organ Size; hladovění; srdce; Keto Acids; 3-methyl-2-oxobutanoátdehydrogenasa (lipoamid); Myocardium; Muscle, Skeletal; mužské pohlaví; 3-Methyl-2-Oxobutanoate Dehydrogenase (Lipoamide); ketonoxidoreduktasy; Multienzyme Complexes; Body Weight; kosterní svaly; krysa rodu Rattus; Animals; Starvation; zvířata; Rats; multienzymové komplexy; Heart; tělesná hmotnost; myokard; Ketone Oxidoreductases